PERAN STAKEHOLDER DALAM PENGEMBANGAN PANTAI PULAU MERAH KABUPATEN BANYUWANGI SEBAGAI DESTINASI WISATA BAHARI - Kurniawati, Risa Amalia Kurniawati; Shaherani , Natasya; Coutrier, Basuhnami Lena Leopold; Sukmawati, Hawa (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
This research aims to determine the efforts of regional tourism development to increase local income. From the research conducted, the Banyuwangi Regency government implementing development of the Red Island Beach has involved the MSME sector. The method used is qualitative descriptive it tries to dig in-depth perspectives of several informants about the role of stakeholders in development of the Red Island Beach Banyuwangi Regency as a marine tourism destination. The data collection techniques used in this study are observation and in-depth interviews. It is to channel the spirit of regional potential-based tourism development to the community of Banyuwangi Regency. The role of the surrounding community in tourism development on Red Island is good. It is seen from the establishment of Pokmas (community groups) on Red Island Beach that actively manage Red Island Beach tourism by upholding accountability and openness aspects for the progress of Red Island tourism. In addition, the community around the Red Island Coast began to improve its economy by establishing a business in Red Island beach tourism, one of which is the establishment of lodging (homestay) by people whose homes are close to the Red Island Beach. The involvement of private parties in the development of Red Island Beach is to help accessibility, empowerment of local communities and utilization of local facilities, promotion, and CSR by building the infrastructure needed by the community and doing environmental care activities, namely the cultivation of coral reefs.